Building smart teams : roadmap to high performance - Beatty, Carol Anne, 1943-; Scott, Brenda A. Barker (Brenda Ann Barker), 1962- (Thousand Oaks, CA : Sage, 2004)
Building Smart Teams is an essential guide to creating a smart team fast. Based on research results from close to 2,000 individuals organized in more than 250 teams, Building Smart Teams identifies the three critical skill sets that teams need and shows how to transfer these skills to a group. The authors’ research and experience shows that, by concentrating on these three critical skills sets, a group is almost certain to become a high performing team quickly.
Includes bibliographical references (p. 189-191) and index.
oif 15/10/14
Loan
Keywords: Teams in the workplace; Performance